ACT-Based Online Intervention for Obsessive-Compulsive Traits, Anxiety, and Depression in Medical Students: A Pilot Study - Athanasios Hassoulas; Rachel McCrum; Angelina Patel; Khaleda Rashid; Prasanna Vaidhaya (BJPsych Open)
Aims: It is estimated that the prevalence of obsessive-compulsive disorder (OCD) in the UK is 2–3%, with a lifetime prevalence of anxiety and/or depression being reportedly much higher (estimated at 20–25%). Prevalence rates within medical students have, however, been reported by numerous studies and systematic reviews to exceed those identified in the general population. The primary aim of the current pilot study was to investigate the efficacy of an Acceptance and Commitment Therapy (ACT)-based online intervention in reducing symptom severity within a sample of medical students screened for OCD, anxiety and depressive traits and symptoms. The hypothesis was that the ACT-based online intervention would reduce symptom severity in participants.